PEMANFAATAN PELAYANAN PERSALINAN TENAGA KESEHATAN - Subchi, Imam (Jurnal Ilmu Administrasi Negara, 2016)
Utilization of Health Services Childbirth Workers. This study aims to examine the use of service delivery by health personnel in Bengkalis. This study is a qualitative research. The informants include: midwives and family couples of childbearing age (the public) and which represents the Department of Health. Based on the survey results revealed that the utilization of delivery care health workers in Bengkalis still not optimal. The difficulty in obtaining health care from midwives. Factors affecting the utilization of delivery care health workers in Bengkalis, among others: the lack of socialization, quality of service and comfort is still lacking, inadequate health care infrastructure, attitude and tranpsortasi difficult conditions.